2017
DOI: 10.5993/ajhb.41.6.2
|View full text |Cite
|
Sign up to set email alerts
|

The Perceived Impact of I am Moving, I am Learning on Physical Activity and Family Involvement: A Preliminary Investigation

Abstract: Participants in the study reported that IMIL contributed to increased levels of PA and family/community involvement. The participants perceived that the use of IMIL helped parents/caregivers and their children become healthier, by improving the whole family's activity levels. Faculty and staff also reported that there were few barriers related to the implementation and sustainability of IMIL use in childcare settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…Articles were published between 1993 and 2019. Studies reported in included articles were delivered in eight high-income countries, with the majority of studies conducted in the USA ( n =19) [ 40 , 41 , 43 , 44 , 46 , 47 , 50 , 52 – 62 , 64 ], followed by the UK ( n =3) [ 39 , 42 , 49 ], Canada ( n =2) [ 20 , 51 ], the Netherlands ( n =2) [ 37 , 45 ], Australia ( n =2) [ 38 , 48 ], Germany ( n =1) [ 63 ], Denmark ( n =1) [ 65 ], and Ireland ( n =1) [ 36 ]. Twelve articles reported on studies that employed qualitative designs [ 36 , 39 , 41 , 46 , 47 , 49 , 52 , 55 , 60 , 61 , 63 , 64 ], eight articles on studies that used quantitative designs [ 40 , 50 , 51 , 53 , 56 59 ], ten articles on studies that used mixed-method designs [ 20 , 37 , 38 , 42 45 , 48 , 54 , 65 ], and one was a summary article which collated previous findings and discussed lessons learned across multiple studies for specific interventions [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Articles were published between 1993 and 2019. Studies reported in included articles were delivered in eight high-income countries, with the majority of studies conducted in the USA ( n =19) [ 40 , 41 , 43 , 44 , 46 , 47 , 50 , 52 – 62 , 64 ], followed by the UK ( n =3) [ 39 , 42 , 49 ], Canada ( n =2) [ 20 , 51 ], the Netherlands ( n =2) [ 37 , 45 ], Australia ( n =2) [ 38 , 48 ], Germany ( n =1) [ 63 ], Denmark ( n =1) [ 65 ], and Ireland ( n =1) [ 36 ]. Twelve articles reported on studies that employed qualitative designs [ 36 , 39 , 41 , 46 , 47 , 49 , 52 , 55 , 60 , 61 , 63 , 64 ], eight articles on studies that used quantitative designs [ 40 , 50 , 51 , 53 , 56 59 ], ten articles on studies that used mixed-method designs [ 20 , 37 , 38 , 42 45 , 48 , 54 , 65 ], and one was a summary article which collated previous findings and discussed lessons learned across multiple studies for specific interventions [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“… Consolidated Framework for Implementation Research (CFIR) [ 72 ]; - Resources/equipment - Training/professional development - Programme support officers. 7–8 years Allar et al, 2017 [ 64 ]; Physical activity intervention- Educational resource ‘I am Moving, I am Learning’ resource. USA; childcare services; physical activity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations